2022
DOI: 10.1007/s11910-022-01178-7
|View full text |Cite
|
Sign up to set email alerts
|

Moving Forward from the COVID-19 Pandemic: Needed Changes in Movement Disorders Care and Research

Abstract: Purpose of Review The COVID-19 pandemic has dramatically affected the health and well-being of individuals with movement disorders. This manuscript reviews these effects, discusses pandemic-related changes in clinical care and research, and suggests improvements to care and research models. Recent Findings During the on-going COVID-19 pandemic, individuals with movement disorders have experienced worsening of symptoms, likely due to decreased access to care, loss of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 87 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…Studies from different countries have demonstrated that individuals with PD experienced worsening motor and nonmotor symptoms during the pandemic [ 8 , 9 , 10 , 11 , 12 , 13 ]. Similarly, the pandemic has negatively affected individuals with other movement disorders such as multiple system atrophy, dystonia, and tic disorders [ 14 , 15 , 16 ].…”
Section: Changes In Care In Response Due To the Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from different countries have demonstrated that individuals with PD experienced worsening motor and nonmotor symptoms during the pandemic [ 8 , 9 , 10 , 11 , 12 , 13 ]. Similarly, the pandemic has negatively affected individuals with other movement disorders such as multiple system atrophy, dystonia, and tic disorders [ 14 , 15 , 16 ].…”
Section: Changes In Care In Response Due To the Covid-19 Pandemicmentioning
confidence: 99%
“…Overall, telemedicine applied to PD patients increased from 9.7% prior to the pandemic to 63.5% during the pandemic [ 17 ]. In fact, we learned from the pandemic that many aspects of healthcare for patients with movement disorders could be provided remotely [ 8 ].…”
Section: Changes In Care In Response Due To the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…All results shown in the experimental section were computed on the test set, by training over 50 different initializations and using the concatenation of the previously defined training and validation sets as training data. The final hyper-parameters of the model used in the experimental section were the following: the size of the crops (128; 256; RGB), number of views (Valdovinos et al, 2022), backbone model (ResNet-50-pre-trained), loss function (cross-entropy-multiclass). For the implementation, we used TensorFlow for the design of the model, with the pre-trained ResNet-50 weights taken from the official Google implementation in TensorFlow Hub, while the pre-trained CRNN weights were taken from the Keras-ocr repository.…”
Section: Handwriting Analysismentioning
confidence: 99%
“…Neurodegenerative disorders, including Parkinson's disease (PD) and Alzheimer's disease (AD), represent a relevant global health issue, and the number of cases is going to increase steeply in prevalence in the next few decades (Armstrong and Okun, 2020;Feigin et al, 2020). Currently, the lockdown restrictions due to the COVID-19 global pandemic have challenged the clinical management of patients affected by neurodegenerative diseases, thus requiring innovative telemedicine approaches (Valdovinos et al, 2022). To this aim, it would be relevant to identify novel telemedicine tools allowing early and objective diagnosis, tracking the severity of the disease and thus improving the overall remote clinical management of patients with neurodegenerative diseases (Chirra et al, 2019).…”
Section: Introductionmentioning
confidence: 99%